Béla Balázs: early film theory "Visible man" and "The spirit of film" - Balázs, Béla 1884-1949 (Berghahn Books, 2011)
Béla Balázs's two works, Visible Man (1924) and The Spirit of Film (1930), are published here for the first time in full English translation. The essays offer the reader an insight into the work of a film theorist whose German-language publications have been hitherto unavailable to the film studies audience in the English-speaking world. Balázs's detailed analyses of the close-up, the shot and montage are illuminating both as applicable models for film analysis, and as historical documents of his key contribution - alongside such contemporaries as Arnheim, Kracauer and Benjamin - to critical debate on film in the 'golden age' of the Weimar silents
Keywords: PERFORMING ARTS / Film & Video / History & Criticism; Motion pictures